Tuition Subsidies in a Model of Economic Growth - Gerson, Philip (IMF Working Papers; Working Paper, 1994)
This paper examines a two-sector aggregative growth model with human capital and educated unemployment. In the model, a tuition subsidy may lead to a long-run decline in the educated fraction of the population, because it may decrease the long-run per capita stock of physical capital in the economy, tending to reduce the output of the education sector and the incentives for workers to enroll in school. Thus, cuts in education subsidies undertaken by countries in Africa for adjustment reasons may actually lead to long-run increases in the educational attainment of their populations.